2018
DOI: 10.2134/agronj2017.12.0726
|View full text |Cite
|
Sign up to set email alerts
|

Forage Potential of Summer Annual Grain Legumes in the Southern Great Plains

Abstract: Winter wheat (Triticum aestivum L.) and perennial warm-season grasses are the primary forage resources for grazing yearling stocker cattle (Bos taurus) in the US Southern Great Plains (SGP). However, low nutritive value of perennial grasses during mid to late summer limits high rates of growth by stocker cattle. In response, there has been a continued search for plant materials with the potential to provide forage high in crude protein (CP) and digestibility during August through September. A broad range of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 110 publications
0
29
0
Order By: Relevance
“…Although temperature and precipitation are highly variable, making it difficult to define a crop that performs well region-wide [17], the mild winter favors cool-season crops for grazing animals [18]. The region is known for its mixed farming practices, producing both livestock and grain.…”
Section: Agroecology and Farming Systems In The Southern Great Plainsmentioning
confidence: 99%
“…Although temperature and precipitation are highly variable, making it difficult to define a crop that performs well region-wide [17], the mild winter favors cool-season crops for grazing animals [18]. The region is known for its mixed farming practices, producing both livestock and grain.…”
Section: Agroecology and Farming Systems In The Southern Great Plainsmentioning
confidence: 99%
“…It covers approximately 3 million hectares of Central Rolling Red Plains of the United States, including parts of Kansas, Oklahoma, and Texas (Bushong, Arnall, & Raun, 2014). In the state of Oklahoma, winter wheat encompasses 75% of the cropland (Patrignani, Lollato, Ochsner, Godsey, & Edwards, 2014) and is produced under rain‐fed conditions (Baath, Northup, Rocateli, Gowda, & Neel, 2018; Vitale, Godsey, Edwards, & Taylor, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Tepary bean is a vining, warm-season legume species originated from the areas of the southwestern United States and northwestern Mexico, that may have value for multiple uses in dryland agricultural systems. Due to its spreading growth habit, and the ability to generate high N biomass with limited soil moisture, tepary bean could be an ideal summer forage for the Southern Great Plains [14]. This first study investigating the application of NIRS to attributes of forage quality in tepary bean showed that the technique could aid in quantifying its role in meeting animal nutrition needs.…”
Section: Parametermentioning
confidence: 99%
“…All three techniques can be employed for rapid NIR-based predictions of CP and IVTD in soybean forage samples, with SVM would be the best choice. Soybean was initially introduced as a forage into the US in the 19th Century, but is now one of the most widely grown grain legumes in the Southern Great Plains [14]. In the last two decades, there has been increased interest from researchers in utilizing soybean as a summer forage in the US [28][29][30].…”
Section: Soybeanmentioning
confidence: 99%
See 1 more Smart Citation